DIFERENTES NÍVEIS DE BETAÍNA NA RAÇÃO DE SUÍNOS SOBRE A ESTRUTURA E ULTRA-ESTRUTURA DA MUCOSA INTESTINAL - Ribeiro, Paulo Roberto (2015)
Abstract We evaluated the effects of increasing levels of betaine (0.0%, 0.1%, 0.2%, 0.3%) on small intestine structure. Fifty-two weaned piglets at 23 days of age and average weight of 5.4 kg were used. We studied four betaine levels and five slaughtered times with three days of interval, considering the weaning day as the initial day (zero day). We evaluated villi height and crypt depth. We observed significant differences (P<0.05) among treatments for villi height in duodenum and for crypt depth in ileum. Regarding post-weaning days, significant differences (P<0.05) in villi height and crypt depth occurred in the three intestinal segments analyzed.